Jožef in Potifarjeva žena v poznoantičnem judovskem in krščanskem slovstvu v semitskih jezikih - Krajnc, Aljaž (Bogoslovni vestnik, 2024)
The paper examines the story of Joseph and Potiphar's wife as depicted in late antique Jewish and Christian literature written in Semitic languages, revealing the development and transmission of motifs between these two traditions. The study analyzes three Jewish texts and six Christian texts, dating from the 2nd to the 7th century CE. Special attention is given to extracanonical motifs, which occasionally transitioned between Jewish and Christian works while also evolving into motifs characteristic of only one of these traditions. The paper includes an appendix with translations of the analyzed texts.
Keywords: Christianity; izvenkanonični motivi; Joseph; Judaism; judovstvo; krščanstvo; late Antiquity; non-canonical motifs; Potifarjeva žena; Potiphar's wife; pozna antika; Semitic languages; semitski jeziki